Right ventricle dysfunction in patients with takotsubo syndrome. (4th February 2022) - Budnik, M; Piatkowski, R; Ochijewicz, D; Zaleska, M; Glowczynska, R; Grabowski, M; Opolski, G
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Pol-tako Background   Takotsubo syndrome  (TTS) is a clinical condition that mimics acute myocardial infarction and is characterised by acute left ventricle dysfunction. However, right ventricle (RV) involvement can also occur.  Purpose    The aim of our study was to compare clinical characteristic, in-hospital complications and in-hospital mortality in patients with TTS with and without RV dysfunction.  Methods    209 consecutive patients with TTS were included in the study. Among them, 13, 9% (29 patients) had RV dysfunction according to echocardiography evaluation. Clinical symptoms at admission to hospital was similar in both groups. There weren't differences in time from onset of symptoms to the hospital admission in both groups.  Results    Patients with RV dysfunction was older (75, 6 vs 69.4y). Left ventricle ejection fraction (LVEF) at 1st and 3rd day of hospitalisation was lower in patients with TTS with RV involvement in comparison to patients without RV dysfunction (37.9 vs 41.9%, 42, 1 vs 47.3% and 46.1 vs 50.9%, respectively). However, at 5th day EF LV was similar in both groups. Tricuspid annular plane systolic excursion (TAPSE) was lower in patients with RV dysfunction at 1st and 3rd day (17 vs 21mm and 19 vs 21.6 mm, respectively). Pulmonary oedema and cardiogenic shock occurred less often in patients with RV involvement (6.9 vs 17.7% and 0 vs 4.4%). In hospital mortality was similar in both groups (3.4 and 2.2%).  Moreover, there was not difference in the length of hospitalisation (11.9 vs 10.1 days).  Conclusions   Right ventricle in patients with TTS can occur in about 14% patients. In addition to impaired RV function also LVEF is more depressed in the first days. However, in hospital mortality is similar.